2021
DOI: 10.1039/d1ra00642h
|View full text |Cite
|
Sign up to set email alerts
|

Fast 3D-lithium-ion diffusion and high electronic conductivity of Li2MnSiO4 surfaces for rechargeable lithium-ion batteries

Abstract: The DFT analysis revealed fast 3D-lithium-ion diffusion pathways and high electronic conductivity in the Li2MnSiO4 surface, and thus paving the way for designing and developing efficient and low-cost rechargeable lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…This finding showed a similar tendency in our prior research for Li 2 MnSiO 4 material. [29] When comparing the PBE‐based predicted bandgap of 1.84 eV (Figures 9 and 11 ) to the PBE+U‐determined bandgap of 2.35 eV (Figures 10 and 12 ). The estimated value of the bandgap of bulk Na 2 SiO 4 from the ordinary PBE‐based PDOS and the corresponding band structure was lower by about half eV relative to the PBE+U results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding showed a similar tendency in our prior research for Li 2 MnSiO 4 material. [29] When comparing the PBE‐based predicted bandgap of 1.84 eV (Figures 9 and 11 ) to the PBE+U‐determined bandgap of 2.35 eV (Figures 10 and 12 ). The estimated value of the bandgap of bulk Na 2 SiO 4 from the ordinary PBE‐based PDOS and the corresponding band structure was lower by about half eV relative to the PBE+U results.…”
Section: Resultsmentioning
confidence: 99%
“…The delocalization problem in the 3d‐orbitals of the Mn atom in Na 2 MnSiO 4 was solved using the DFT+U approach following the previous studies. [ 29 , 30 ] Despite the fact that determining the correct U‐value is a difficult task, Table 1 displays the computed E g with several U‐values ranging from 1 to 6 eV with 0.5 intervals, with the U‐value of 1.5 eV (E g =2.35 eV) being fixed for further analysis. [29] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A research on the development of Li 2 MnSiO 4 cathode demonstrated that the different synthesis methods were used to prepare phase pure cathodes with good electrochemical performance [129,130] . It was suggested to investigate the chemical composition and the complex structural distortion during the redox reaction of the cathode, in order to design high‐performance cathode materials for LIBs [131] . Furthermore, Cheng al [38] .…”
Section: Silicates: An Alternative Viable Cathode?mentioning
confidence: 99%
“…[129,130] It was suggested to investigate the chemical composition and the complex structural distortion during the redox reaction of the cathode, in order to design high-performance cathode materials for LIBs. [131] Furthermore, Cheng al. [38] reviewed a variety of techniques for the modification of the physical and electrochemical properties of Li 2 MnSiO 4 cathode, but it still poses several practical challenges, hence thorough studies should be carried out in order to understand the electrochemical barriers of the cathode material.…”
Section: Mnsio 4 Cathodes For Libsmentioning
confidence: 99%